Green fiscal reform for a just energy transition in Latin America - Michael Jakob; Rafael Soria; Carlos Trinidad; Ottmar Edenhofer; Céline Bak; Daniel Bouille; Daniel Buira; Hernan Carlino; Veronica Gutman; Christian Hübner; Brigitte Knopf; André Lucena; et al. (Kiel Institute for the World Economy (IfW), 2018)
Green fiscal reforms would contribute to climate change mitigation, increase the economic efficiency of national tax systems and provide additional public revenues. Some countries in Latin America have already taken first steps towards green fiscal reforms. This paper provides an overview of the major challenges for the successful implementation of such reforms and discusses how they could be overcome. The authors first discuss the role of country-specific economic and political enabling conditions that need to be in place for successful implementation for green successful reforms. Second, they emphasize the importance of comprehensive reform plans that include all relevant ministries and agencies and are well-aligned with other policy objectives, such as energy security and industrial development. Third, they highlight how appropriate sequencing and gradualism could lower implementation costs and hence increase the political feasibility of green fiscal reforms. Finally, the authors analyze the potential impacts of green fiscal reforms on the distribution of income and discuss transfer schemes that could avoid adverse outcomes for the poorest parts of the population. They use these four dimensions to illustrate why recent reform efforts in selected Latin American countries have been successful or have failed, respectively.
Keywords: H23; E62; Q54; N16; Q48; 330; green fiscal reform; energy subsidies; Latin America; multi-objective climate policy; sequencing; distribution